2017
DOI: 10.1016/j.ribaf.2017.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal loan growth, credit information sharing and systemic risk in Asian banks

Abstract: This paper investigates the interplay of abnormal loan growth, credit reporting system and systemic risk in banking. Based on a sample of publicly traded banks in Asia from 1998 to 2012, higher abnormal loan growth leads to higher systemic risk one year ahead. A closer investigation further suggests that better credit information coverage and private credit bureaus can stem the buildup of bank systemic risk one year ahead due to higher abnormal loan growth. Eventually, this paper offers some supports to streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 44 publications
(8 reference statements)
1
14
0
Order By: Relevance
“…Cucinelli (2016) also found that the relation between credit growth and Non-Performing Loans (NPL) was positive, particularly during the recession in Italy. Soedarmono et al (2017) showed a similar result in nine Asian countries between 1998 and 2012. Finally, recent studies (Laidroo and Mannasoo, 2017;Papadamou et al, 2018) indicated loan growth caused a greater loan loss provision and insolvency in EU countries.…”
Section: Introductionsupporting
confidence: 60%
“…Cucinelli (2016) also found that the relation between credit growth and Non-Performing Loans (NPL) was positive, particularly during the recession in Italy. Soedarmono et al (2017) showed a similar result in nine Asian countries between 1998 and 2012. Finally, recent studies (Laidroo and Mannasoo, 2017;Papadamou et al, 2018) indicated loan growth caused a greater loan loss provision and insolvency in EU countries.…”
Section: Introductionsupporting
confidence: 60%
“…[47] revealed that credit information sharing reduces bank credit risk in both low and high income countries in Africa. [48] stated that the significance of strengthening credit information coverage and the function of private credit bureaus in Asian countries to mitigate the negative impact of unusual loan growth on bank systemic dependability. [38] explained that the banking industry of Ghana employs varied techniques to mitigate its credit risk, Such as the utilize of the credit referencing bureau.…”
Section: Credit Bureau Reportmentioning
confidence: 99%
“…More specifically, NPL rises from the previous year's abnormal loan growth, which tends to reduce solvency. Besides, with regards to systematic risk, Soedarmono et al (2017) show that abnormal credit growth increases the bank systemic risk one year ahead in 9 Asian countries. Hitherto, there are still many conflicting results between abnormal loan growth and bank risk-taking in developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors state that in case of aggressive credit expansion, increase lending may potentially come from lowering interest rates, relaxing collateral requirements, loosening credit standards, or a combination of them. This growth from these mechanisms, consequently, may have adverse effects on bank risks (Dell'Ariccia & Marquez, 2006;Ogura, 2006;Soedarmono et al, 2017). Until now, there are relatively few works that study this major topic from an individual bank perspective (Foos et al, 2010) or/and in emerging markets (Amador et al, 2013;Gosh, 2010;Kashif et al, 2016).…”
Section: Introductionmentioning
confidence: 99%